2020
DOI: 10.1055/s-0040-1701463
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Inadequate Birth Intervals in the BRISA Birth Cohort, Brazil

Abstract: Objective To determine the prevalence of inadequate birth interval and its associated factors in the BRISA study. Methods Cross-sectional study using data from the BRISA cohort. Birth interval was categorized into “adequate” (≥ 2 years or < 5 years between births), “short interval” (< 2 years) and “long interval” (≥ 5 years). The analysis of the factors associated with short and long birth intervals used multinomial logistic regression. Results The prevalence of adequate birth interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
4
2
1
Order By: Relevance
“…Findings of this study revealed that more than half (56%) of women in the study area were practicing short birth interval, which is consistent with the study conducted in Uganda (52.4%) ( 5 ), Southwest Ethiopia (59.9%) ( 7 ), Kasala, Eastern Sudan (60.6%) ( 33 ), and Southern Ethiopia (57%) ( 34 ). However, the result of this study is higher than the findings of the study conducted in rural Bangladesh (24.6%) ( 31 ), Nepal (23%) ( 35 ), Brazil (17.1%) ( 36 ), Northern Ethiopia (23.3%) ( 26 ), and Arsi Zone, Southeast Ethiopia (17.3%) ( 29 ). This discrepancy could be explained by the difference in the measurement of short birth interval, study settings, and interventions made across countries.…”
Section: Discussioncontrasting
confidence: 75%
“…Findings of this study revealed that more than half (56%) of women in the study area were practicing short birth interval, which is consistent with the study conducted in Uganda (52.4%) ( 5 ), Southwest Ethiopia (59.9%) ( 7 ), Kasala, Eastern Sudan (60.6%) ( 33 ), and Southern Ethiopia (57%) ( 34 ). However, the result of this study is higher than the findings of the study conducted in rural Bangladesh (24.6%) ( 31 ), Nepal (23%) ( 35 ), Brazil (17.1%) ( 36 ), Northern Ethiopia (23.3%) ( 26 ), and Arsi Zone, Southeast Ethiopia (17.3%) ( 29 ). This discrepancy could be explained by the difference in the measurement of short birth interval, study settings, and interventions made across countries.…”
Section: Discussioncontrasting
confidence: 75%
“…While rural and urban areas of Nigeria were 20.7% and 20.3% respectively. This result is higher than the SBI reported in Rwanda, but lower compared to ndings in some other African countries [5,11] as well as in Brazil [12]. The observed differences could be attributed to the prevalent socio-geographical and cultural differences in the studied areas.…”
Section: Discussioncontrasting
confidence: 70%
“…A few factors have been reported to be associated with birth intervals. Some of these may be direct factors such as frequency of sexual activity, use of contraceptives, postpartum in fecundability, abortion, and sterility while indirect factors may include socioeconomic and cultural factors [12,13]. Interbirth interval is also in uenced by sociodemographic, economic, and birth history [6].…”
Section: Introductionmentioning
confidence: 99%
“…Pernyataan ini sesuai dengan WHO yang juga merekomendasikan orang tua untuk menunggu paling tidak 24 bulan, atau kelahiran dengan interval 33 bulan atau lebih namun dibawah 5 tahun sebelum mencoba kehamilan berikutnya. Jarak kelahiran dibawah 24 bulan dianggap jarak kelahiran pendek dan jarak kelahiran diatas 5 tahun dianggap jarak kelahiran panjang, baik jangka pendek maupun jangka panjang dianggap sebagai jarak kelahiran inadekuat (2). Jarak kelahiran inadekuat merupakan faktor risiko untuk kematian ibu dan bayi, dan dianggap lebih berisiko dari semua metode keluarga berencana, kecuali sterilisasi dan abortus (3).…”
Section: Pendahuluanunclassified